2002
DOI: 10.3168/jds.s0022-0302(02)74224-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein Metabolism in Lactating Goats Subjected to the Insulin Clamp

Abstract: A model of Leu and protein metabolism by the mammary gland and hind leg of lactating goats was constructed and evaluated from data collected by using [15N, 1-13C]Leu kinetics measured during amino acid (AA) infusion and a hyperinsulinemic-euglycemic clamp (IC). Goats were given continuous intravenous infusions of either saline or AA (65 g/d) for 7.5 d and from d 5 to 7.5 goats were subjected to IC. Arteriovenous kinetics were monitored on d 4 and 8 by continuous infusion (8 h) of [15N, 1-13C]Leu. Milk protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 18 publications
0
35
2
Order By: Relevance
“…As a primary outcome of Lys degradation, Glu then acts as a transamination precursor for Asp, Ala and Ser in particular for the NEAA and for the BCAA from the EAA. Indeed, in ruminants, Leu has been shown to be a major intermediate in N-transfers linked to the high transamination rate in many tissues including muscle (Holtrop et al, 2004) and the MG (Bequette et al, 2002). Indeed, in goats injected with a single dose of […”
Section: Discussionmentioning
confidence: 99%
“…As a primary outcome of Lys degradation, Glu then acts as a transamination precursor for Asp, Ala and Ser in particular for the NEAA and for the BCAA from the EAA. Indeed, in ruminants, Leu has been shown to be a major intermediate in N-transfers linked to the high transamination rate in many tissues including muscle (Holtrop et al, 2004) and the MG (Bequette et al, 2002). Indeed, in goats injected with a single dose of […”
Section: Discussionmentioning
confidence: 99%
“…Insulin plays an important role in regulating the partitioning of nutrients to the mammary gland (McGuire et al, 1995;Mackle et al, 2000;Bequette et al, 2002). These studies showed that a hyperinsulinaemic euglycaemic clamp (HEC) increased milk protein output in concentrate-fed ruminants, suggesting that amino acid (AA) partitioning to and/or AA utilisation within the mammary gland increased under HEC conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the nutritional status of the animals might also affect their response to insulin (Bequette et al, 2002). This is largely untested in early lactating ruminants fed fresh forage: the few existing studies reported no increase in milk protein concentration or yield in lactating dairy cows (Back et al, 2003) and sheep with the HEC alone, or with supplemental protein (Back et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations